A novel water-saving and drought-resistance rice variety promotes phosphorus absorption through root secreting organic acid compounds to stabilize yield under water-saving condition. (15th September 2021) - Bi, Junguo; Hou, Danping; Zhang, Xianxian; Tan, Jinsong; Bi, Qingyu; Zhang, Kangkang; Liu, Yi; Wang, Feiming; Zhang, Anning; Chen, Liang; Liu, Guolan; Liu, Zaochang; et al.
Abstract: More than 70% of global rice production depends on irrigation water, which has brought on a progressive reduction in the groundwater table. Further groundwater withdrawal are unsustainable for future rice production. Sustainable rice production calls for the use of resource-saving and environmentally friendly rice varieties. This study investigated the morphological and physiological mechanisms of biomass and tissue phosphorus accumulation in a water-saving and drought-resistance rice variety (Hanyou73) and a normal paddy rice variety (Hyou518) under different water management regimes. The two rice cultivars were grown in pot experiments carried out with factorial combinations of three water regimes, conventional irrigation (high irrigation rate, HR), 60% of conventional irrigation (medium irrigation rate, MR), and 20% of conventional irrigation (low irrigation rate, LR) for four-years. While the grain yield of Hanyou73 was similar as Hyou518 under HR, it was significantly higher than Hyou518 under MR and LR. Under deficit irrigation, the tissue-specific biomass of Hanyou73 was higher than that of Hyou518, and the total P accumulation of Hanyou73 was 70% greater than that of Hyou518. Meanwhile, the root growth, root oxidation activity, and absorption area of Hanyou73 under the MR and LR treatments were significantly higher than those of Hyou518. Analysis of root exudate metabolites revealed an abundance of organic acids produced by the Hanyou73 roots under, which may account for its higher P uptake. Overall, the findings of this study indicate that Hanyou73 promoted P uptake to maintain higher yields under deficit irrigation. The higher P uptake by Hanyou73 may be related to its altered root physiology, which may be the mechanism by which Hanyou73 adapts to water saving irrigation conditions and maintains its yield traits. Highlights: Sustainable rice production requires the cultivation of Water-saving and drought-resistance rice varieties. Hanyou73" maintained high yield and phosphorus levels under low-irrigation condition. Higher phosphorus uptake supported "Hanyou73" yield. The physiological mechanism underlying the high phosphorus uptake is an increase in root oxidation and absorption area. The root exudates of "Hanyou73" contained high levels of organic acids and anions.